STRATEGI PERBANKAN SYARIAH DALAM MENINGKATKAN INKLUSI KEUANGAN DI INDONESIA - Nengsih, Novia (AL-ITTIFAQ Jurnal Ekonomi Syariah, 2023)
This study aims to analyze the strategy of Islamic banking in increasing inklusi keuangan in Indonesia. This research is a field research with a qualitative approach. Collecting data using interviews, documentation, and observation. The data analysis technique used descriptive qualitative analysis. The result of the study found that the strategies used by Islamic banking in increasing inklusi keuangan were by channeling financing to the real sector, strengthening microfinance, developing partnership programs through zakat, infaq, sodaqoh, qard al-hasan, and other social funds, as well as developing linkage programs with Small and Medium Enterprises (SMEs).